Assemblage Theory and the Capacity to Value: An Archaeological Approach from Cache Cave, California, USA. Issue 1 (11th January 2017) - Robinson, David
Abstract : New discoveries from a Californian cave have found a remarkable assemblage of cached perishable and other artefacts. Comprised of baskets, cordage, bone, antler, leather, food residues and other materials, the assemblages are dispersed through four caves in the largest ever cache discovered in the borderland region attributable to the native Californian linguistic group known as the Chumash. This paper develops a methodology based upon DeLanda's philosophy of assemblages and Graeber's anthropological theory of value. Importantly, following Normark, it is argue that assemblage theory needs to be operationalized into a methodological approach in order to apply it archaeologically. This methodology illustrate how a capacity analysis of the Cache Cave assemblage relates to values within the society which cached it by revealing the relational capacities within assemblages and relative capacities between them. Importantly, as a scalable approach, capacity analysis allows the investigation of the heterogeneous dynamics within complex societies.